ANALISIS TINGKAT PERSAINGAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA SEPEDA MOTOR YAMAHA DAN HONDA - Sumitro, Yanus; Soekotjo, Wahjono (Universitas PGRI Adi Buana, 2018)
The purpose of this study were: 1) To know is there any difference in consumer satisfaction Yamaha and Honda; 2) To determine the factors that distinguish consumer satisfaction Yamaha and Honda. This study used primary data obtained using a questionnaire. Data were analyzed using independent samples t compare means test, chi square, descriptive statistics with SPSS version 15.0. The results showed that the quality of service from Yamaha and Honda motorcycles rated as good by most customers. While the results of comparative tests between the service quality Yamaha motorcycle with Honda based on the dimensions of reliability, keresponsifan, assurance, empathy and tangible as well as quality of service overall there are significant differences. Importance based on cartesian diagram analysis of service quality performance dimension of Yamaha motorcycles by Honda, that respond dimension, a dimension that is considered important by customers Honda with Yamaha motorcycles, but the performance of the dimensions keresponsifan not as expected, either by the customer Yamaha motorcycle and Honda motorcycle customers. This indicates the need for improvement of service quality, particularly in the dimensions respond.